(untitled) (Research, Society and Development, 2020)
Objective: to present the form of action and interaction of SARS-CoV-2 with human cells and describe the main studies on the treatment for Covid-19. Methodology: a review was carried out in the Science Direct-Elsevier and PubMed databases with analysis of experimental works in vitro and in vivo, review, technical notes and clinical research records. The terms used were: Coronavirus, COVID-19, SARS-CoV-2 associated with pathogenesis, clinical studies and treatment. Results: Many studies are under development to understand the pathogenesis of the virus and to seek efficient therapies to contain COVID-19, such as chloroquine, hydroxychloroquine, Arbidol, favipiravir, remdesivir, among others. Conclusion: This article reviewed the mechanisms of action of SARS-CoV-2 in order to provide information for a better understanding of the actions taken by several researchers in therapy against COVID-19. Many drugs are undergoing clinical trials to see if they can minimize the serious effects of the virus on the population.